(untitled) - Cascio, Wayne F. (New York, 1989)
This text gives in-depth coverage of major HRM topics, and discusses the strategic use of human resource management function with emphasis on cost/benefit aspects of HR practice. Current examples are given to support the arguments, focusing upon real people in real organizations. A different split-sequential case starts each chapter - events lead to a climax, the case stops and the reader is asked to predict the outcome; conclusions are presented at the end of each chapter. New to this edition is a chapter on workplace diversity, with examples from Xerox, Pacific Bell, J.C. Penny and other companies. There is also coverage of the legal environment, which includes changes in law, court rulings, and implications for HR practice, such as job analysis under the Americans with Disabilities Act. In addition, "ethical dilemma" sections in each chapter require students to choose a course of action and defend their reasons for doing so.
Keywords: Personnel management,Quản trị nhân sự